Pet problems: Biological and economic factors that influence the release of alien reptiles and amphibians by pet owners. Issue 6 (21st August 2018) - Stringham, Oliver C.; Lockwood, Julie L.
Abstract: The number of alien reptiles and amphibians introduced and established worldwide has increased over the last decades. The legal pet trade is now the dominant pathway by which individuals of these species arrive in their non‐native locale. Despite its importance, specific factors of pet trade pathway that influence the release (introduction) of exotic reptiles and amphibians have not yet been examined. We set out to identify broadscale and easily measured biological and economic factors that influence the release of these exotic pets by their owners. We hypothesize that biological factors reflect the cost of care, and economic factors reflect the value that owners place on their pet, both of which can influence the probability when a pet is released. We collected life history and economic data on the 1, 722 species of reptiles and amphibians sold within the US as pets over the last 18 years. We also compiled a list of pet trade‐attributed releases in the US (i.e., all free‐living species regardless of whether they successfully established). We used boosted regression trees to correlate species release status with their life‐history traits and economic attributes ( r 2 = 0.51, AUC = 0.89). We found that species with a high probability of being released were imported at higher quantities over our period of record, have a relatively large adult mass and commanded cheaper retail prices. The number imported and price interacted with longevity and adult mass to produce nonlinear increases in release probability. The most important interaction revealed that large‐bodied species imported in high quantities have a three times higher release probability compared to large‐bodied species imported in lower quantities. Policy implications . Our results provide guidance towards targeting exotic pet reptile and amphibian species that are at a high risk of being released. Species that are both prevalent in the pet trade and large‐bodied or long‐lived have the highest probability of being released. This will aid in developing education and policy solutions aimed at decreasing the rate at which these pets are released, thus curtailing the invasion process before these species can establish and impacts can occur.